Humanitariniai mokslai jėzuitų švietimo sistemoje - Ulčinaitė, Eugenija (Literatūra, 2007)
The Jesuit order, officially titled Societas Jesu, was established in 1540. The order became the main prop, putting into effect the principal decrees formulated by the Tridentine church Council in the years between 1545 and 1563. The principal tasks of the activity of Societas Jesu became the fight against Protestant Reformation as well as the fight against the reform of the Catholic Church itself.The above mentioned tasks were to be put into effect with the help of the organizing of modern educational system, the establishing of new types of schools, i.e., colleges, as well as by the adequate preparation of teachers, and the writing and publishing of suitable textbooks.In a typical college comprised of five classes, where three classes were dedicated to the studies of grammar, poetics and rhetoric, the following subjects were taught: the Latin and Greek languages, the reading of Classical authors, the encouraging of independent creation, while following the best examples of Classical literature. The Jesuit educational system considered the humanities to form the basis for the advanced studies of philosophy and theology.A thoroughly designed educational structure as well as a good preparation of the pedagogues and the training of the creative abilities of pupils determined the popularity of Jesuit colleges, which significantly contributed to the fostering of the traditions of the humanities in Lithuania between the 16th and 18th centuries.